IHI ID 20 Sustaining system-level high reliability for CLABSI: impacts of standardization, human factors, and direct observation of key processes. (December 2018) - Stalets, Erika; Hausfeld, Jackie; Casper, Tammy; Demmel, Kathleen; Cooks, Andrea; Alexander, Christopher; Simon, Katherine; Geiser, Maria; Sitterding, Mary; Simmons, Jeffrey
Abstract : Background: From 2007 to 2015, in our large, quaternary childrens hospital, significant improvement was achieved and sustained in our rate of central line associated blood stream infections (CLABSI). However, a dramatic rate increase occurred in 2015; the control chart centerline shifted from 0.62 to 1.95/1000 line days despite process compliance consistently at/above 95%. Comprehensive investigations determined several system-level factors contributed to the deterioration, including widespread practice variation as units implemented uncoordinated changes without full appreciation of human factors implications. Objectives: Reduce inpatient CLABSI events by 20% or more by the end of FY17. Methods: A multidisciplinary retreat convened with key stakeholders to assess current state and redesign the CLABSI process bundle. Redesign of workflows, supply kits, and a multi-phase implementation plan included human factors considerations, 2:1 training, and peer coaching. Standardized, near real-time, multidisciplinary event review huddles focused on identifying themes. Bundle monitoring shifted from predominately chart review to direct observations. Results: From FY16 to FY17, CLABSI events decreased 28.7% (122 to 87), for an estimated 1, 925, 000 cost savings. An additional 20% decrease was achieved in FY18, 70 events (9 35 000 saved) resulted in a downward centerline shift in the system-level control chart. Observed bundle compliance was 82% compared to 95% via chart review. Conclusions: Uncoordinated improvement efforts and inconsistent training contributed to a significant rise in CLABSI events. System-wide standardization informed by human factors considerations coupled with a process monitoring paradigm shift to direct observation led to significant and subsequently sustained improvement in CLABSI events in a single, quaternary childrens hospital.